A Prospective Analysis of Vasoreactivity and Mortality in WHO Group 3 Pulmonary Hypertension - Daniel J. Strick; Carl Tanba; Meredith A. Kaplan; Nicholas S. Hill; Harrison W. Farber; David Condon; Ioana R. Preston (Pulmonary Circulation, 2025)
ABSTRACT Prognostic markers of Group 3 pulmonary hypertension (PH) remain largely unknown. In this study, we evaluate clinical data to provide a comprehensive profile of patients with Group 3 PH and evaluate the potential use of vasoreactivity testing as a prognostic tool within this population. We hypothesized that patients with a stronger vasoconstrictive component of their pulmonary vascular disease would have a more favorable prognosis. Patients were given inhaled nitric oxide during their right heart catheterization to determine if they met the European Respiratory Society guidelines for having a positive vasoreactivity test as defined for patients with Group 1 pulmonary arterial hypertension (PAH). While vasoreactivity response is proven to predict survival in subgroups of PAH, there was no significant relationship between change in mean pulmonary artery pressure (mPAP) during acute vasodilator challenge and survival within our cohort. On the contrary, patients with larger decreases in pulmonary vascular resistance (PVR) during the acute vasodilator challenge were at a significantly higher risk of mortality. The data suggests that the change in PVR during acute vasodilator challenge may be a better indicator of survival in patients with WHO Group 3 PH than the change in mPAP.